Islet Regeneration and Pancreatic Duct Glands in Human and Experimental Diabetes - Overi, Diletta; Carpino, Guido; Moretti, Marta; Franchitto, Antonio; Nevi, Lorenzo; Onori, Paolo; De Smaele, Enrico; Federici, Luca; Santorelli, Daniele; Maroder, Marella; Reid, Lola M.; Cardinale, Vincenzo; et al. (Frontiers in Cell and Developmental Biology, 2022)
Contrasting evidence is present regarding the contribution of stem/progenitor cell populations to pancreatic regeneration in diabetes. Interestingly, a cell compartment with stem/progenitor cell features has been identified in the pancreatic duct glands (PDGs). The aims of the present study were to evaluate pancreatic islet injury and regeneration, and the participation of the PDG compartment in type 2 diabetic mellitus (T2DM) and in an experimental model of diabetes. Human pancreata were obtained from normal (N=5) or T2DM (N=10) cadaveric organ donors. Experimental diabetes was generated in mice by intraperitoneal injection of 150mg/kg of streptozotocin (STZ, N=10); N=10 STZ mice also received daily intraperitoneal injections of 100µg of human recombinant PDX1 peptide (STZ+PDX1). Samples were examined by immunohistochemistry/immunofluorescence or RT-qPCR. Serum glucose and c-peptide levels were measured in mice. Islets in T2DM patients showed β-cell loss, signs of injury and proliferation, and a higher proportion of central islets. PDGs in T2DM patients had a higher percentage of proliferating and insulin+ or glucagon+ cells compared to controls; pancreatic islets could be observed within pancreatic duct walls of T2DM patients. STZ mice were characterized by reduced islet area compared to controls. PDX1 treatment increased islet area and the percentage of central islets compared to untreated STZ mice but did not revert diabetes. In conclusion, T2DM patients show signs of pancreatic islet regeneration and involvement of the PDG niche. PDX1 administration could support increased endocrine pancreatic regeneration in STZ. These findings contribute to defining the role and participation of stem/progenitor cell compartments within the pancreas.